Ideology and Idolatry - Razauskas, Dainius (Religija ir kultūra, 2019)
A series of articles has already been published in recent years by the author on the notion of cosmogony as implied by Lithuanian term for it, sutvėrimas. This polysemous term has at least three gross branches of meanings: not only the most usual ‘fencing (in, off, around)’ but also ‘coagulation, solidifying, hardening’ and ‘catching, clenching (by hand)’, and all of these meanings are reflected in traditional views of creation. However, both the very cosmogony and still more various processes of smaller scale corresponding to different meanings of sutvėrimas (and the verb sutverti) may have also negative sense, that of stagnation, hardening, stiffness, stop of the life flow. Hence the notion of freedom, conversely, as softening, thawing, melting and free flow. Therefore, human being either stays in this definitively hardened world which has become a prison to his soul or begins to loosen his grip on it and to thaw gradually himself. On the cosmic scale, this hope and objective is eschatological, and on the personal scale, soteriological, that is, aimed at deliverance and freedom which in this sense is the opposite of cosmogony. The very ‘createdness’ in its different hues then is conceived negatively, as ‘madeness’ and artificiality, as antithesis of freedom and obstacle to it. And its principal manifestations in the inner world, then, are ideology and idolatry, the two aspects of one and the same phenomenon looked at from slightly different angles. That is exactly the subject of this article (which continues two previous, “Without ground, without support” (Razauskas 2022a) and “Ideas, Ideals, and Ideologies” (Razauskas 2022b)).